2019
DOI: 10.1007/s12144-019-00480-x
|View full text |Cite
|
Sign up to set email alerts
|

Extravert individualists or introvert collectivists? Personality traits and individualism and collectivism in students in Poland and Ukraine

Abstract: The aim of this research was to analyse the connections between personality traits and horizontal and vertical forms of individualism and collectivism, regarded as social orientations, in two national groups of students. The analyses were conducted in the context of psychosocial functioning in the academic environment. A total of 210 students were examined including 109 of Polish nationality and 101 of Ukrainian nationality. Despite the historical and geographical proximity of both countries, we predicted that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Likewise, Realo, Allik and Vadi also found that collectivism is associated with greater agreeableness; adding conscientiousness to the list as well (Realo, Allik, & Vadi, 1997 ). While an agreement between these findings and ours is promising, it should be noted that the relationship between cultural orientations and personality traits likely varies from place to place (Tychmanowicz et al, 2021 ). For example, because individuals with collectivistic cultural orientations may be more strongly influenced by, or more sensitive to, their culture than individuals with individualistic orientations, the relationships between personality and culture may very across cultural orientations (Triandis, 2001 ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Likewise, Realo, Allik and Vadi also found that collectivism is associated with greater agreeableness; adding conscientiousness to the list as well (Realo, Allik, & Vadi, 1997 ). While an agreement between these findings and ours is promising, it should be noted that the relationship between cultural orientations and personality traits likely varies from place to place (Tychmanowicz et al, 2021 ). For example, because individuals with collectivistic cultural orientations may be more strongly influenced by, or more sensitive to, their culture than individuals with individualistic orientations, the relationships between personality and culture may very across cultural orientations (Triandis, 2001 ).…”
Section: Discussionsupporting
confidence: 84%
“…The present study helps fill this gap, and the studies that do exist mostly agree with the findings herein. For example, Tychmanowicz, Filipiak and Sprynska reported that agreeableness was associated with less individualism and higher collectivism (Tychmanowicz, Filipiak, & Sprynska, 2021 ). Other researchers reporting similar findings have suggested that this association arises from a predisposition towards social dominance (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…As culture is effective in acquiring and developing personality traits [22], and it brings the individual a unique identity within the general rules. In addition, each culture represents a different way of life, and the diversity of the cultures differentiates individuals [23][24][25][26]. In other words, the unique nature, boundaries and diversity of each culture form an individual's frame of reference and prepare the basis for individual differences.…”
Section: Introductionmentioning
confidence: 99%
“…Extraversion is characterised by a high social need, ability to connect, assertiveness and a tendency to talk and be active (Tychmanowicz et al, 2021). On the other end of this dimension is introversion.…”
mentioning
confidence: 99%